Asuhan Keperawatan Pada Pasien Dengan Chronic Kidney Disease (CKD) di Ruang Interne RSUD Prof.Muhammad Yamin,SH Pariaman - Mona Mona; Linda Marni; Debby Silvia Dewi; Hilma Yessi (CV. ITTC INDONESIA, 2026)
Chronic Kidney Disease (CKD) is a growing global health problem. According to the WHO, by 2025, approximately 674 million people worldwide will be living with chronic kidney disease, or approximately 9% of the global population. It is predicted that CKD could become the fifth leading cause of death worldwide, with a mortality rate of approximately 1.48 million deaths per year. In Indonesia, the prevalence of chronic kidney disease is 0.38%, with 713,783 people suffering from CKD. In West Sumatra, the prevalence of Chronic Kidney Disease is 0.40%. Approximately 13,834 cases were reported. In 2025, CKD ranked first at Prof. H. Muhammad Yamin, SH, Pariaman Regional General Hospital, with 335 cases. Chronic Kidney Disease is a condition in which the kidneys fail to function optimally for a prolonged period. The method used was a case study with a homicide approach on one patient, Mrs. L., in the internal ward of Prof. H. Muhammad Yamin, SH, Regional General Hospital, from February 22-25, 2026. The results of the five-day study revealed the following diagnoses: hypervolemia, ineffective breathing pattern, ineffective peripheral perfusion, constipation, and disturbed body image. After treatment, the patient's condition is expected to improve, indicated by a reduction in shortness of breath, edema, fatigue, and pain.